Grainger & Allison's diagnostic radiology : a textbook of medical imaging - Grainger, R.G; Allison, D.J; Potchen, E. James; Baert, A (London : Churchill Livingstone, 1999)
This CD-ROM contains the complete text of the third edition Grainger and Allison's Diagnostic Radiology including all photographs, line illustrations, tables and references.
System requirements: PC ; 486 66 Mhz Processor, 12 MB of RAM (16 MB recommended), 8 MB of free hard disk space, Microsoft Windows 3.x, Windows 95, Windows 98 or Windows NT, 15' SVGA color monitor, Double speed CD-ROM drive, Sound Card (only recommended for Tutorial)
System requirements: Macintosh ; 68040 Processor, 12 MB of RAM, 8 MB of free hard disk space, System 7.x, 14' SVGA color monitor, Double speed CD-ROM drive
Keywords: Diagnostic imaging